If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + y = 5 Solving 2 + y = 5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + y = 5 + -2 Combine like terms: 2 + -2 = 0 0 + y = 5 + -2 y = 5 + -2 Combine like terms: 5 + -2 = 3 y = 3 Simplifying y = 3
| 9x-18=-27 | | 4x^3+12x=0 | | 22+x=4-8x | | 4=3t-2 | | 4r^2+32r=0 | | 194-2x=43x+24 | | 3x-6=-99 | | -0.4x+3=1 | | -21=x-12 | | -21=x-13 | | -2(2s-3)-6=-2(4s+9)-2 | | 3+3y=-12 | | 82=-x+11 | | y=9-4 | | 2a-b=ac+3b | | 12=-6-x | | 8n+5n=65 | | y=2(4)-7 | | 14x+78-(32+12x)=134 | | 0.8w-0.4w+0.1w=2 | | y=2(3)-7 | | 62=15+x | | (3m-2)(m-2)=m(3m-8)+3m | | r+22=14 | | 51=-x+15 | | 3x+5y^15= | | 5x+4+6x+9=10x+5 | | 6x-(5x+5)=-1 | | 42=-x-15 | | 4(5x-25)=20(x-5) | | -3x+5= | | (y-4)(y-4)=49 |